PKM perbaikan alat-alat rumah tangga listrik di Kabupaten Bantaeng - Muliadi Muliadi; Dyah Darma Andayani (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
The community service activity aims to provide training to repair household electrical and electronic equipment to youth organizations in Bonto Tiro Village, Sinoa District, Bantaeng Regency. The methods used in this service are: lectures, questions and answers, discussions and for the training used demonstration methods. To resolve partner problems, a training activity to repair electrical household appliances based on project work has been done. This activity carried out to provide knowledge about the basic concepts of electricity and electronics, basic electronic components, and how to repair several electrical household appliances. The results achieved in this community service activity were 15 members in youth productive age from skilled and competent partners in repairing household electrical appliances, have already understand of how to use electrical and electronic measuring instruments, how to use electrical and electronic equipment, managing workshop , K3, and entrepreneurship.